Dispersal of natural regeneration in some Piai-invaded areas of mangrove forests in Sarawak - Jawa, R.R.; Srivastava, P.B.L. (Elsevier, 1989)
Stands of four different ages (1, 3, 6 and 9 years after felling) were selected in Rejang Mangrove Forest Reserve, Sarawak, to study the dispersal of mangrove natural regeneration in areas which were prone to Piai (Acrostichum spp.) invasion or were already infested by this weed fern. Data were recorded on regeneration of economically important species, Piai cover, mother trees, lobster mounds and drainage pattern. The two most common species recorded were Rhizophora apiculata and Bruguiera parviflora. The abundance of seedlings in different age-classes was in the following order: 9 > 6 > 1 > 3 years after felling, whereas according to inundation-class, it was in order of III > IV > V. The number of seedlings was insufficient to adequately restock the respective areas. The abundance of mother trees followed the sequence of seedling pattern in different age-classes. The most dominant height-class for commercial species was H1 (30 cm-150 cm). The lobster mounds in inundation-class III were less closely packed and relatively lower in height than in inundation-classes IV and V. This was partly responsible for the increase in Piai abundance in ascending order of inundation classes. There is a need to determine the optimum number of mother trees and an economically viable control measure for eradicating piai for sustained management of these forests.